A survey of understory birds at a rice field and a mixed dipterocarp forest in Kuching Sarawak - Karim, Nurqamareena; Yee, Ling Chong; Jayasilan, Mohd-Azlan; Mohd Fizl sidq, Ramji (Malaysian Society of Applied Biology, 2018)
Habitat modification can lead to reduction of biodiversity. This survey aimed to determine the diversity of understory birds and their feeding guilds at rice field plantation and mixed dipterocarp forest. The understory birds were mist-netted from March to May 2017 and resulted in 110 individual birds of 32 species from 19 families. Among them, five species are legally protected and three species are considered Near Threatened under the IUCN Red List (2017). Preliminary analysis suggests most birds are habitat specialist. Only two omnivore species [i.e. Yellow-vented Bulbul (Pycnonotus goiavier) and Pied Fantail (Rhipidura javanica)] were caught at both habitats. Cream-vented Bulbul (Pycnonotus simplex) and Brownthroated Sunbird (Anthreptes malacensis) were the most predominant bird species captured in Santubong National Park (SNP), whereas Chestnut Munia (Lonchura atricapilla) was the dominant species at rice field in Stunggang Melayu Village, Lundu. Although omnivores and insectivores dominated both habitats, three species of nectarivores were caught at SNP. SNP showed higher bird species diversity and mean richness (H’=3.045; 0.935) compared to rice field (H’= 2.565; 0.7257) (t-test; p = 1.1432x10-6). This preliminary study provides baseline information on bird species diversity and habitat preference at two different habitats in Western Sarawak.